2021
DOI: 10.1111/infa.12422
|View full text |Cite
|
Sign up to set email alerts
|

Symbolic play provides a fertile context for language development

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 100 publications
3
10
0
Order By: Relevance
“…In pretend play, parents regarded their role as a 'partner in fun' , but during real activities regarded their role as a teacher or monitor. Notably, they also found that parents asked more questions during the pretend activity, consistent with what has been found for the cohort studied in the current study across two longitudinal time points (Creaghe et al, 2021). Taggart et al suggested that the use of questioning may indicate the provision of learning opportunities for the child, and also 'scaffold the construction of shared meanings in pretend play' (p. 779).…”
Section: Id3 Symbolic Playsupporting
confidence: 87%
See 3 more Smart Citations
“…In pretend play, parents regarded their role as a 'partner in fun' , but during real activities regarded their role as a teacher or monitor. Notably, they also found that parents asked more questions during the pretend activity, consistent with what has been found for the cohort studied in the current study across two longitudinal time points (Creaghe et al, 2021). Taggart et al suggested that the use of questioning may indicate the provision of learning opportunities for the child, and also 'scaffold the construction of shared meanings in pretend play' (p. 779).…”
Section: Id3 Symbolic Playsupporting
confidence: 87%
“…Such styles are categorised by the use of distinct linguistic frames that, in the case of pretence, serve to draw children into conversation or, in the case of real activities, direct behaviour. Creaghe et al (2021) analysed the conversational dynamics of the dyads studied by Quinn and Kidd (2019). Consistent with Reissland (1998), they found that in symbolic play caregivers used language with their infants that drew them into the interaction significantly more than in functional play; specifically, questions (e.g., would you like some tea?)…”
Section: Introductionsupporting
confidence: 52%
See 2 more Smart Citations
“…The relationship between symbolic play and language development has been frequently discussed (Bergen & Mauer, 2000; Hirsh-Pasek et al, 2004, 2008; Quinn et al, 2018). In English, symbolic play naturally elicits caregivers’ use of the linguistic and communicative behaviors that assist children’s essential language development, such as conversational turn-takings, interrogatives, and mimetics (Creaghe et al, 2021). Our results have shown that the passives in symbolic play have discrete reference to the actions and the scene, assisting children to map thematic roles in the actions and events.…”
Section: Discussionmentioning
confidence: 99%